The effect of fibroblast growth factor 21 on a mouse model of bovine viral diarrhea - Zhao, Dan; Song, Yu-Hao; Song, Jin-Ming; Shi, Kun; Li, Jian-Ming; Diao, Nai-Chao; Zong, Ying; Zeng, Fan-Li; Du, Rui (Frontiers in Veterinary Science, 2023)
Previously, we researched that bovine viral diarrhea virus (BVDV) induced a very significant increase in fibroblast growth factor 21 (FGF21) expression in mouse liver and that FGF21 was increased in the peripheral blood of BVD cattle and BVD mice. To determine the role of FGF21 in relieving clinical symptoms and inhibiting the intestinal damage caused by BVDV in BVD development in mice, BALB/c mice were intraperitoneally injected with cytopathic biotype (cp) BVDV-LS01 (isolated and identified by our group) to establish a BVD mouse model. The role of FGF21 in the BVD mouse model was investigated by injecting the mice with FGF21. The animals were divided into control, BVDV challenge, BVDV + FGF21, BVDV + FGF21Ab (anti-FGF21 antibody), and BVDV + IgG (immunoglobulin G) groups. The stool consistency, the degree of bloody diarrhea, histopathological changes, inflammatory cell infiltration, weight loss percentage, and detection of BVDV in the feces of the mice were examined, and the pathological changes and inflammatory cytokine expression were analyzed. The results showed that after BVDV challenge, the average BVD mouse model score of the BVDV mice was 11.6 points. In addition to mild diarrhea and tissue damage, BVDV was detected in the stools of 13 BVDV mice. Only two mice in the control group had scores (both, 1 point each). The comprehensive scoring results demonstrated the successful establishment of the BVD mouse model. FGF21 alleviated the clinical symptoms in the BVD mice and significantly improved weight loss. Furthermore, FGF21 inhibited the BVDV-induced leukocyte, platelet, and lymphocyte reduction while inhibiting the expression of BVDV-induced inflammatory factors. In the BVD mice, FGF21 promoted duodenal epithelial cell proliferation, thereby significantly improving the damage to the cells. In conclusion, FGF21 exerted a good therapeutic effect on the BVD mouse model.